2015
DOI: 10.1021/acs.jpcc.5b08524
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Interdependence of Structure and Properties of Nanocomposites of Multiwall Carbon Nanotubes with Polyaniline

Abstract: Structure–property relationships of nanocomposites of multiwall carbon nanotubes (MWCNTs) and polyaniline (PANI) doped with dodecylbenzenesulfonic acid (DBSA) are studied and discussed in terms of contribution of the PANI phase properties. Two phases of PANI-DBSA with different properties, such as a shell-wrapping carbon nanotube and separate neat PANI-DBSA domains, are revealed for the first time in the nanocomposites with a high or medium PANI-DBSA content. In the nanocomposites with lower PANI-DBSA contents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 70 publications
0
24
0
1
Order By: Relevance
“…The band at 1323 cm −1 is associated with the elongation of the C‐N + bonds, which suggests the polymer protonation and evidences its conducting state. Finally, the band at 1569 cm −1 is related to the elongation of the C=C bond …”
Section: Resultsmentioning
confidence: 99%
“…The band at 1323 cm −1 is associated with the elongation of the C‐N + bonds, which suggests the polymer protonation and evidences its conducting state. Finally, the band at 1569 cm −1 is related to the elongation of the C=C bond …”
Section: Resultsmentioning
confidence: 99%
“…The weak bands at 262, 395, 682, and 1010 cm −1 are characteristic of VO 2 , which are identified as, in order, the bending vibrations of V=O and bridging V−O−V, the stretching modes of doubly coordinated V 2 ‐O entity and terminal V=O bond . With regard to the pure PANi and VO 2 @PANi, all the visible peaks at 415, 524 (the C−N−C out‐of‐plane torsions), 574, 607 (the deformations of amine and benzenoid ring), 1162 (the C−H in‐plane bending vibration), 1228, 1336 (the stretching modes of C−N and C−N .+ ), 1387 (the cross‐linked phenazine units), 1459 and 1586 cm −1 (the C=N and C=C stretching species) can be attributed to the PANi phase . It should be noted that the intensity of the peak at 607 cm −1 is much higher than that at 574 cm −1 for PANi, while an opposite case is detected for VO 2 @PANi, which is in agreement with Wan's analysis, indicating the imperfect structure of polymer chain in the obtained PANi.…”
Section: Resultsmentioning
confidence: 99%
“…Structure differences between the conducting polymer in pure and composite states were confirmed for different (nano)composites [16,17,19,23,25,26,29,[30][31][32][33]. For example, from the XRD-spectra of doped polyaniline and its nanostructured composite with polycarbonate (PC), we found that its degree of crystallinity in the pure state was about 3 times lower, and 6.…”
Section: Structure-property Relationship Of the Nanocompositesmentioning
confidence: 82%
“…6b) and also polypyrrole (Fig. 6b) an increased crystallinity of ICP in the nanocomposite, especially at its low contents, was observed [29,35].…”
Section: Structure-property Relationship Of the Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation